A COMPARATIVE STATISTICAL STUDY OF MAJOR DISCIPLINE CHOICE OF SCIENCE FRESHMAN STUDENTS - Temesgen, Zewter (The Ethiopian Journal of Education, 2025)
This article compares the preference of freshman students of Addis Ababa University for the disciplines Architecture,Biology, Chemistry, Geology, Mathematics, Pharmacy, Physics, Statistics and Technology under the past socialist" and the present market economy systems.